2020
DOI: 10.1017/s0022215120000948
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory tympanotomy in sudden sensorineural hearing loss for the identification of a perilymphatic fistula – retrospective analysis and review of the literature

Abstract: AbstractObjectiveThe diagnostic value of exploratory tympanotomy in sudden sensorineural hearing loss remains controversial. This study and review were performed to identify the incidence of perilymphatic fistula in patients with sudden sensorineural hearing loss. The effectiveness of tympanotomy for sealing of the cochlear windows in cases with perilymphatic fistula was evaluated. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Heilen et al treated ninety patients with sudden SHL using exploratory tympanotomy and the sealing of the oval and round windows [ 14 ]; 10 patients (11 percent) were identified with a perilymphatic fistula, corresponding to the results obtained from their review (13.6 percent). In two cases only, the pre- and post-operative audiological evaluation results showed a significant hearing improvement after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heilen et al treated ninety patients with sudden SHL using exploratory tympanotomy and the sealing of the oval and round windows [ 14 ]; 10 patients (11 percent) were identified with a perilymphatic fistula, corresponding to the results obtained from their review (13.6 percent). In two cases only, the pre- and post-operative audiological evaluation results showed a significant hearing improvement after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In two cases only, the pre- and post-operative audiological evaluation results showed a significant hearing improvement after treatment. They concluded the absence of significant improvement after an exploratory tympanotomy and the sealing of the membranes for patients with a definite perilymphatic fistula presented with SHL [ 14 ]. Our findings were the opposite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our experiences, PLF repair surgery using TEES for idiopathic PLF can be performed without complications under clear visualization and a wide field of view. Heilen et al (12) reported that there is no significant hearing improvement after exploratory tympanotomy with sealing of the round window for patients with SSHL. Prenzler et al (13) reported that exploratory tympanotomy with sealing of the round and oval windows is useful in patients with profound SSHL.…”
Section: Discussionmentioning
confidence: 99%